Extracellular Vesicles Derived from Adipose Mesenchymal Stem Cells Promote Peritoneal Healing by Activating MAPK-ERK1/2 and PI3K-Akt to Alleviate Postoperative Abdominal Adhesion - Manyu Shi; Hengchen Liu; Tingting Zhang; Mingzhao Zhang; Xin Tang; Zenan Zhang; Wenjun Lu; Shulong Yang; Zhitao Jiang; Qingbo Cui; Zhaozhu Li (Stem Cells International)
Peritoneal regeneration and repair can alleviate postoperative intraperitoneal adhesions, and mesenchymal stem cells (MSCs) have demonstrated the potential for peritoneal repair and regeneration. However, extracellular vesicles (EVs) are the main carriers for the MSC activity. Thus far, the roles of MSC-derived EVs on peritoneal repair are not well understood. To investigate the therapeutic effect of adipose-derived mesenchymal stem cell-derived EVs (ADSC-EVs) in peritoneal injuries, ADSC-EVs were injected in vivo via the tail vein of rats. The antiadhesion effects were evaluated following abdominal surgery. In addition, the levels of the peritoneal fibrinolysis system were determined via enzyme-linked immunosorbent assay. Expression differences in inflammatory and apoptotic markers were detected using immunofluorescence. The expression of extracellular matrix-related indexes and peritoneal healing were observed using immunohistochemistry. In vitro, rat peritoneal mesothelial cell proliferation was assessed via a 5-ethynyl-2-deoxyuridine assay. Cell migration was determined using scratch wound and transwell assays. Related signaling networks were estimated based on sequencing and bioinformatics analyses. The roles of the MAPK–ERK1/2 and PI3K–Akt signaling networks were analyzed using immunoblotting. This is the first report of the effectiveness of ADSC-EVs in the treatment of postoperative adhesions. ADSC-EVs were incorporated in vitro and induced rat peritoneal mesothelial cell proliferation and migration. This was mediated by stimulation of the MAPK–ERK1/2 and PI3K–Akt axes. ADSC-EVs promote the healing of the injured peritoneum, suggesting a promising therapeutic approach for peritoneal adhesions.